„Nieziszczone narodziny”. Cixous i Irigaray, czyli kobiety z Czarnego Kontynentu - Szopa, Katarzyna (Postscriptum Polonistyczne, 2020)
The aim of the article is to discuss the phenomenon of a ‘newly born woman’ that appears in the writing of the French theoreticians of gender, Hélène Cixous and Luce Irigaray. The author of the article distinguishes between the views of the two researchers and aims to reveal the specificity and uniqueness of each of them. This approach goes beyond the frames of ‘essentialism’ designed by Anglo-American critics of the eighties.